North American Integration after 20 Years - G. M. Kostyunina (MGIMO University Press, 2015)
Formation of the North American Free Trade Area (NAFTA) among the three countries - the U.S., Canada and Mexico is the most striking example of successful development of integration processes in the Western Hemisphere. This year NAFTA marks the 20th anniversary of its foundation (1994). NAFTA covers trade in goods, services and movement of capital, intellectual property rights, environmental cooperation and labor cooperation. Its main advantages for member countries related to the dynamic growth of regional trade and investments, promoting the growth of industrial production (capital-intensive and high-tech industries in the U.S. and Canada, and labor-intensive industries in Mexico), increase the investment attractiveness of the economies of member countries and the promotion of employment. But there are costs, both general and specific to the individual member countries. Common costs are primarily asymmetrical level of economic interdependence, where mutual economic relations are the most developed between the U.S. and Canada, the U.S. and Mexico, and the least developed between Mexico and Canada due to historical conditions. Other costs are the differentiation in the levels of economic development, in volumes of overall GDP and per capita, population and size of the territory. But despite the costs, integration processes are successfully developed and repeatedly raised the issue of deepening economic integration between the U.S., Canada and Mexico. So, in 2000, there was put forward the concept of creating the North American community as an economic and security community by 2010, and in 2005 proposed the idea of a common currency called the Amero. But these proposals did not come true. On the agenda - the possibility of signing a new, more expanded NAFTA+, and even in the last year - the possibility to form a customs union under NAFTA.